Redefining Baseline for Forestry Projects Under Clean Development Mechanism - Kant, Promode; Katwal, R. P. S. (Indian Forester, 2003)
Inclusion of afforestation and reforestation as eligible activities in Clean Development Mechanism (CDM) under the Kyoto Protocol has necessitated change in the existing definition of the baselines. The Subsidiary Body for Scientific and Technical Advice (SBSTA) constituted under the United Nations Framework Convention on Climate Change (UNFCCC) has suggested five options for this purpose for discussion and adoption at the ninth Conference of Parties to UNFCCC. The authors have analyzed the relative merits of these options and have argued that on account of scientific desirability , technical feasibility and economic considerations , the most appropriate definition for baselines for forestry projects under the CDM is a variant of one of the options that defines the baseline as the "scenario that represents the net changes in carbon stocks within the project area in the most likely prospective land use at the time the project starts. It is subject to the condition that the construction of the scenario be based on the land suitability classification , land ownership and legal and policy restraints at the beginning of the project and , further , that the project shall take all necessary and possible measures to reduce the emission of methane and nitrous oxide gases due to project activities".